Pola Aktivitas Fisik Mahasiswa Ilmu Keolahragaan Universitas Negeri Surabaya Sebelum dan Selama Pandemi Covid 19 - Hakim, Abdul Aziz; Sudijandoko, Andun; Agustin, Ressy (Smart Education, 2021)
This study aims to determine the sports pattern of the State University of Surabaya before and during the Covid-19 pandemic. The sample in this study was the students of the Faculty of Sports Science Unesa class of 2018 and 2019 totaling 200 students. The questionnaire used in this study is a questionnaire that has been calculated and passed the test of the value of its validity and reliability using SPPS version 23. The results in this study indicate that the data is homogeneously distributed but not normal, then the Wilcoxon nonparametric test is then carried out to test the hypothesis. The results of the nonparametric Wilcoxon test showed that there was a significant difference in the physical activity pattern of the Surabaya State University Sports Science students before and during the Covid-19 pandemic with a P value of < 0.05. The conclusions obtained in this study are that the physical activity patterns of Sports Science students at the State University of Surabaya before and during the Covid-19 pandemic were different, and during the Covid-19 pandemic the pattern of physical activity decreased when compared to before the Covid-19 pandemic.